Dietary marine-derived long-chain monounsaturated fatty acids and cardiovascular disease risk: a mini review. Issue 1 (December 2016) - Yang, Zhi-Hong; Emma-Okon, Beatrice; Remaley, Alan
Abstract Regular fish/fish oil consumption is widely recommended for protection against cardiovascular diseases (CVD). Fish and other marine life are rich sources of the cardioprotective long-chain n-3 polyunsaturated fatty acids (n-3 PUFA) eicosapentaenoic acid (C20:5 n-3; EPA) and docosahexaenoic acid (C22:6 n-3; DHA). The lipid content and fatty acid profile of fish, however, vary greatly among different fish species. In addition to n-3 PUFA, certain fish, such as saury, pollock, and herring, also contain high levels of long-chain monounsaturated fatty acids (LCMUFA), with aliphatic tails longer than 18 C atoms (i.e., C20:1 and C22:1 isomers). Compared with well-studied n-3 PUFA, limited information, however, is available on the health benefits of marine-derived LCMUFA, particularly in regard to CVD. Our objective in this review is to summarize the current knowledge and provide perspective on the potential therapeutic value of dietary LCMUFA-rich marine oil for improving CVD risk factors. We will also review the possible mechanisms of LCMUFA action on target tissues. Finally, we describe the epidemiologic data and small-scaled clinical studies that have been done on marine oils enriched in LCMUFA. Although there are still many unanswered questions about LCMUFA, this appears to be promising new area of research that may lead to new insights into the health benefits of a different component of fish oils besides n-3 PUFA.